BEOWULF AS EARLY EXAMPLE OF ALLITERATION IN LINGUISTICS - Nizomova, Zebo (Innovative Development in Educational Activities, 2023)
Alliteration is considered to be one of the most important stylistic devices not only on English language but also in linguistics. Alliteration refers to constant repetition of similar initial consonant sounds one another not only in sentences but also in phrase. The first appearance of alliteration could be seen in Old English epic poem which is called “Beowulf”. According to the vast majority of linguistics, Beowulf is foundation of alliteration. This article investigates the epic poem “Beowulf” and highlights the key examples of alliteration in “Beowulf”.